2019
DOI: 10.3390/ani9100746
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxytocin, Cloprostenol or Buserelin in Semen Doses on Sow Fertility

Abstract: Simple SummaryEfficient pork production relies on a consistent supply of market pigs. However, many sows experience a seasonal infertility during the hotter months, resulting in fewer pigs produced and a seasonally constrained pork supply. The present study examined the impact of supplementing boar semen with different hormones in order to combat sow seasonal infertility. The results confirmed a seasonal infertility, in that litter sizes were reduced for sows bred during May to August, but that this adverse ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…The effects of supplementation of semen extender with oxytocin on sperm motility have been determined in previous studies (Duziński et al, 2014;Fuchs et al, 1989;Manjarín et al, 2019). In the present study, the oxytocin concentration of 0.5 U/ml did not significantly decrease sperm motility and vigour, but the concentrations of 1.0 U/ml and 2.0 U/ml significantly decreased sperm motility.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…The effects of supplementation of semen extender with oxytocin on sperm motility have been determined in previous studies (Duziński et al, 2014;Fuchs et al, 1989;Manjarín et al, 2019). In the present study, the oxytocin concentration of 0.5 U/ml did not significantly decrease sperm motility and vigour, but the concentrations of 1.0 U/ml and 2.0 U/ml significantly decreased sperm motility.…”
Section: Discussionsupporting
confidence: 63%
“…The treated gilts were superior to the controls by 6.3 per cent in pregnancy rate and by 56 born piglets to each 100 first inseminations (Hühn et al, 1977). In another study, the same addition of 5 IU oxytocin to pooled semen doses containing 3 × 10 9 sperm in 80 ml extender at first insemination, increased litter size in 154 multiparous Landrace ×Large White sows (Manjarín et al, 2019). The addition of oxytocin in boar fresh or frozen-thawed semen did not affect the sperm motility or acrosomal integrity (Fuchs et al, 1989;Okazaki et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this matter, the role of SP-OXT could be to stimulate the secretion of prostaglandin E2 by the endometrium of sows [ 49 ], which has immunosuppressive activity and, therefore, contributes to creating a tolerogenic environment in the uterus [ 29 ]. Some of the above empirical studies found that the supplementation of AI-doses with OXT also improved litter size in addition to farrowing rates [ 31 , 33 , 34 ]. This increase in litter size was not found in the present study, perhaps because the SP-OXT concentrations measured in the present study were significantly lower than those used in the aforementioned studies, which ranged from 0.04 to 0.1 IU/mL.…”
Section: Discussionmentioning
confidence: 99%
“…However, the seasonal effect is more important when using breeds with a lower level of genetic selection or in latitudes with a higher thermal or humidity variation [ 11 , 19 , 20 ]. Indeed, we detected a seasonal effect in studies using commercial breeds (Landrace, Large White, and their crosses) [ 21 , 22 , 23 ]. However, when studying the sperm cryopreservation of the autochthonous breed, Gochu Asturcelta (Northern Spain), the seasonal effect was small and, interestingly, it reflected on a lower freezability in winter [ 19 ].…”
Section: Introductionmentioning
confidence: 99%